2022
DOI: 10.1136/spcare-2022-003815
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine for prevention and treatment of chemotherapy-induced peripheral neuropathy (CIPN): systematic review and meta-analysis

Abstract: IntroductionDuloxetine has previously been reported to be promising in the setting of chemotherapy-induced peripheral neuropathy (CIPN). The aim of this study was to conduct a comprehensive systematic review and meta-analysis, on the use of duloxetine in prevention and treatment of CIPN.MethodsPubMed, Embase and Cochrane CENTRAL were searched from database inception up until April 2022. Articles were included in this review if they reported on duloxetine use in the setting of CIPN, in a multiarm comparative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…The literature search in PubMed was restricted to articles published in peer-reviewed journals and written in English. In addition to the systematic literature search, we evaluated studies manually obtained primarily by reviewing previously reported clinical guidelines and systematic reviews ( 10 , 11 , 13 , 17 , 25 ). Two authors independently screened each study for eligibility, and disagreements among reviewers were resolved through discussion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search in PubMed was restricted to articles published in peer-reviewed journals and written in English. In addition to the systematic literature search, we evaluated studies manually obtained primarily by reviewing previously reported clinical guidelines and systematic reviews ( 10 , 11 , 13 , 17 , 25 ). Two authors independently screened each study for eligibility, and disagreements among reviewers were resolved through discussion.…”
Section: Methodsmentioning
confidence: 99%
“…They note that duloxetine is the only medication with sufficient evidence supporting its use in CIPN patients experiencing established pain ( 9 , 10 ). Recent studies suggest that its effectiveness is comparable to that of a placebo ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] However, a recent meta-analysis shows that duloxetine's efficacy in treating CIPN is not considerably more remarkable than the placebo effect, and caution should be used concerning its side effects. 10,11 Based on the above discussion, the search for a proven treatment is critical.…”
Section: Introductionmentioning
confidence: 99%
“…CIPN is one of the most frequent dose-limiting side effects of chemotherapy 2 4. Although numerous clinical trials have been conducted to prevent or treat CIPN using various targeted drugs, previous systematic reviews with direct comparisons have failed to demonstrate the efficacy of drug therapy in the prevention or treatment of CIPN 36–38. No systematic reviews of CIPN have indirectly compared the available pharmacological options for its prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%